Marriott international inc. equity research - consolidating a leading position amid recovery - Correia, Hugo Filipe Pais Rabaça Nabais (2022)
This report, which is part of a broader Equity research on Marriott International Inc., in tends to analyze the fundamentals that drive the value of the target company and that will subsequently serve as base for its respective valuation. Understanding the true value drivers of Marriott’s business model and how those may be impacted by broader factors becomes extremely relevantatatimeofsignificantvolatilityanduncertaintyincapitalmarkets.Byexaminingthetargetcompany’shistoricalperformance as well as the macroeconomic and industry-specific outlook as a means to elaborate the necessary forecasts of Marriott’s value drivers, it will be concluded that the North American hotel chain’s core competencies place it on the fore front to benefit from present industry dynamics and consolidate its leading positio nin hospitality.